Bio-efficacy of Certain Insecticides Sequence on Cotton Sucking Pests and Pink Bollworm - Prasad, B. Ram; Ashwini, D. (International Journal of Bio-resource and Stress Management, 2021)
The field trials were conducted for two consecutive years during kharif, 2018 and 2019 seasons in the Regional Agricultural Research Station, Warangal, Telangana, India. The susceptible hybrid RCH-2 was grown during both the years of study. Among the treatments, significant (25.4%) reduction of aphids was recorded in neem oil, clothianidin and flonicamid sequential spray. The sequence chlorpyriphos, flonicamid and clothianidin achieved superior efficacy against jassids with 32.3% reduction over control during the two seasons. The highest reduction (25.2%) of thrips was observed in neem oil, clothianidin, flonicamid sequential spray. The incidence of whitefly was low during the experimental period, however, the highest white fly reduction (15.0%) was observed in chlorpyriphos, flonicamid, clothianidin spray. The lowest number of PBW larvae per 10 green bolls was observed in profenophos, spinetoram, chlorpyriphos+cypermethrin sequential spray that reduces up to 61.9% incidence. The lowest number of (38.5) damaged locules per 100 fully opened bolls were observed in profenophos, spinetoram, chlorpyriphos+cypermethrin sequential spray. But, the highest seed cotton yield (1414 kg ha-1) as well as benefit cost ratio (1.02) was recorded in chlorpyriphos, flonicamid, emamectin benzoate, clothianidin, indoxacarb+acetamiprid sequential spray. The study further revealed that, initial control of sucking pests menace especially jassid was crucial in deciding the cotton yield as compared to later stage pink bollworm menace. During both the years, it was noticed that during peak incidence of jassid, the treated plot with flonicamid against jassid in first instance had given highest seed cotton yield.